Observing wetland microenvironments as part of a whole in Southern Africa - Wood, Adrian; Thawe, Patrick; Mbewe, Alick (CGIAR, 2024)
Governments in Southern Africa tend to under-estimate the importance of small seasonal wetlands for food security, but NEXUS Gains observes that these microenvironments are a crucial lifeline during drought years